TRANSFER OF HETEROGENEOUS KNOWLEDGE ALONG THE DUAL-NETWORK OF MNCS - Baskici, Cigdem (PEOPLE: International Journal of Social Sciences, 2017)
The literature on knowledge transfer in multinational companies (MNCs) reveals little of to what extent different types of knowledge are exchanged by the subsidiaries in the dual-network of the MNC. The objective of this paper is to fill this gap and to present the kinds of knowledge network of the MNC. This research is based on case study. An MNC is selected which of headquarter is located in Turkey and subsidiaries in 15 different countries including England, China, S. Africa. A wide variety of knowledge can be transferred from subsidiaries to the MNC. The study deals with the knowledge transfer having a potential of usage in product innovation. Using network analysis, the paper reveals that what types of knowledge subsidiaries are willing to search for and transfer through their network ties. The three types of knowledge are distributed and exchanged by subsidiaries along with the dual-network of MNC. Intensity and pervasiveness of knowledge flows display any differences between three types of knowledge. Additionally, knowledge flows’ route could be defined. Thus, where knowledge was travelling in an environment could be revealed. This finding is especially important for managers to establish the new knowledge routes.